« Where are the boys? Have you found them? » : La confluence comme rencontre manquée dans Moonlight de Harold Pinter - Adeline Arniac (Études Britanniques Contemporaines, 2017)
Harold Pinter’s decision to stage what originated in a clinical case study, with Deborah’s awakening from a 29-year-long coma, triggers a reflexion on physical forms of dispossession and exposure. By making the diseased body perceptible, the play achieves a retrieval from invisibility, fully acknowledging Deborah’s presence on stage. However, the attention is also drawn to her body in its materiality and to the dispossession caused by embodiment. Exposing the materiality of the body reveals its fragility and vulnerability, and acts as a reminder that we are all potentially dependent. This forced surrender of total control shows that exposure becomes a necessary way to acknowledge the other, beyond any attempts at understanding him/her through language and knowledge.